Aerobic fitness in top-class soccer referees - Castagna, C.; Bizzini, M.; Araújo Póvoas, C. S.; Schenk, K.; Büsser, G.; D'Ottavio, G. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to examine the aerobic fitness status of top-class male soccer officials using a cross-sectional design and known population group constructs. Fifty-two field referees (FRs, age 38.4 ± 3.3 years; height 181 ± 5.6 cm; body mass 76.8 ± 6.8 kg; body mass index [BMI] 23.4 ± 1.7 kg·m-2; body fat 20.4 ± 3.6%; and international refereeing experience 5 ± 3.5 years) and 104 assistant referees (ARs, age 37.8 ± 4.1 years; height 176.9 ± 7.5 cm; body mass 72.1 ± 7.4 kg; BMI 23 ± 1.6 kg·m-2; body fat 19.2 ± 3.6%; and international refereeing experience 7 ± 3.8 years) from 53 National Football Associations worldwide, and candidates of the preliminary open-list developed by the FIFA Refereeing Department for the 2014 World Cup Final Tournament, were tested for aerobic fitness in laboratory conditions with a progressive speed treadmill test to exhaustion. Large (+8.54%, d = 0.8) and small (+3.1%, d = 0.3) differences in absolute (L·min-1) and relative (ml·kg-1·min-1) VO2max were found between FR and AR, respectively. Trivial differences (d = 0.07) were shown in running economy (RE) (6 minutes at 8 km·h-1) between AR and FR. Using the scaling notation (b = 0.64), medium and significant differences were found between match officials for VO2max and RE (FR > AR; d = 0.6 and 0.67, respectively). Using receiver operating characteristic curve statistics, cutoff values of 3.93 L·min-1 and 50.6 ml·kg-1·min-1 were detected in absolute and relative VO2max for the FR and the AR (FR > AR), respectively. The FR showed superior aerobic fitness compared with AR. Training prescription should consider intensities at anaerobic threshold speed (14 km·h-1, 91% heart rate max) when aerobic fitness development is the aim in elite officials.